Quality Evaluation of Sports Events from the Perspective of Viewers: an Example of Lithuanian Basketball Selection Matches (Laisvalaikio tyrimai, 2021)
This article examines the quality of sport events in the matches of Lithuanian basketball teams. The theoretical part analyzes the concept, significance, quality of sports events and the factors that determine it. A comparative analysis of quality assessment models was performed and the most appropriate quality model for sports events was selected for this study - SPORTSERV (Theodorakis & Kambitsis, 1998; Theodorakis et al., 2001; Theodorakis et al., 2008). A questionnaire was prepared based on this model. The survey collected and analyzed data, discussed results, and presented conclusions.Question arises – how to properly assess the quality of a sporting event?Object of work –  quality of matches events in Lithuanian basketball teams (Lithuanian national basketball men's and women's national teams, Lithuanian youth).The aim of the work – to evaluate the quality of a sports event from the point of view of spectators: on the example of Lithuanian basketball team matches.The goals: 1. To define the concept and meaning of a sports event and it‘s quality. 2. To identify the factors determining the quality of sports events from the theoretical point of view. 3. To reveal the quality of Lithuanian basketball teams: Lithuanian national basketball men's and women's teams, Lithuanian youth match events held from 01.09.2019 to 01.06.2020 from the point of view of spectators.Conclusions: 1. The definition of a sporting event can be distinguished as the gathering of sports participants, spectators at a certain place and time at which they watch or participate in a sports competition. Sports events are divided according to - the level of the game (professional or amateur), only one sport (European and world championships of various sports) or several sports (Olympic Games). The significance of sporting events can be divided into direct (economic) and indirect (social, cultural, political). The quality of a sporting event can be described as the satisfaction of spectators and participants with the event and one of the factors determining the demand for this type of event. 2. After analyzing the scientific literature of different authors as the factors determining the quality of sports events can be distinguished - material things (palpability), security, event location, emotion, event time, information about the event, discounts, food quality, staff competencies and friendliness, labeling, design, empathy, reliability (reputation of sports event organizers), level of play and experience of athletes, price, access (location of the sports event and it’s attractiveness). 3. The research revealed that the quality of the research was well assessed by the spectators in the Lithuanian basketball team matches. Analyzing the satisfaction of men and women in the matches of Lithuanian basketball teams, it was noticed that the satisfaction of men was higher than that of women. The highest scores of respondents were in the safety category (the location and environment of the event are safe). Where most efforts should be made in organizing Lithuanian basketball team matches, respondents named the category of material things (modernity of the arena, sound system, ventilation, etc.). This category had the lowest scores for both womens and mens.Key words: quality of sports events, sport events, matches of Lithuanian basketball teams.